Ethnomathematics Exploration of Jong Sailboat Shape As a Traditional Game in the Riau Islands - Syarmadi Syarmadi; Nur Izzati (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2020)
The Jong Sailboat is a traditional game of the Riau islands' Malay culture. This game developed in various areas whose territories have beaches. In the Jong Sailboat game, mathematical elements can be explored, especially in the Jong Sailboat's shape. Mathematical practice in culture is known as ethnomathematics. Ethnomathematics studies can be obtained through exploration, exploring the field to get more knowledge from a situation. Through Jong Sailboat's exploration, mathematical concepts and elements are found in it. So this research aims to explore ethnomathematics in the shape of a Jong Sailboat as a traditional game in the Riau Islands. This type of study is qualitative research with an ethnographic approach. The subjects in this study were makers of traditional game crafters and the shape of the Jong Sailboat. Data collection is done by interview, observation, and documentation, with the main instrument of study, are the researchers themselves. The data is then analyzed by referring to Miles and Huberman's design by reducing data, presenting data, and conclusions/verification. The results found a mathematical practice in geometrical shapes in triangles, rectangles, and mathematical concepts in the way of translations, acute angles, right angles, trigonometry, straight lines, and slope. This exploration can enrich ethnomathematics science, which is also found in the form of Jong Sailboats.